Penatalaksanaan Fisioterapi pada Kasus Frozen Shoulder Sinistra dengan Modalitas Ultrasound, TENS, Terapi Latihan dan Muscle Release - Syamsul Ari Wicaksono; Totok Budi Santoso; Gemilang Gemilang (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Frozen shoulder is a musculoskeletal disorder of the glenohumeral joint characterized by pain, stiffness, and decreased range of motion, generally occurring at the age of 45-60 years and often associated with low physical activity or comorbid diseases. This study aims to evaluate the effectiveness of physiotherapy interventions in the form of a combination of ultrasound, Transcutaneous Electrical Nerve Stimulation (TENS), muscle release, and exercise therapy in a 72-year-old male patient with left frozen shoulder. The method used is a case study with interventions including ultrasound, TENS, muscle release, and active, passive, isometric, pendulum, walking finger, and passive stretching exercises given during three meetings. The results showed a decrease in silent, pressure, and motion pain, as well as a decrease in the SPADI score indicating an increase in shoulder function. The implications of this study indicate that the combination of electrotherapy and exercise therapy modalities can provide positive results in reducing pain and increasing functional activity in cases of frozen shoulder, although further research is needed with more varied intervention designs and durations to strengthen these findings.